Expert perspective: Highlights on myeloma cell therapy from the American Society of Hematology Annual Meeting 2019. Issue 4 (19th June 2020) - Kunacheewa, Chutima; Manasanch, Elisabet E.
Abstract: Autologous stem cell transplantation has been part of standard of treatment in multiple myeloma for 2 decades. The data showed improving progression‐free survival and overall survival. Despite the improvement of new drugs, myeloma patients continue to relapse New cell therapy, chimeric antigen receptor T‐cell therapy have been explored in heavily pretreated patients. In this commentary, we highlight studies presented at the American Society of Hematology (ASH) Annual Meeting held in Orlando, FL in December 2019. Abstract : One possible mechanism of relapsed disease is the downregulation of surface B‐cell maturation antigen (BCMA) by gamma secretase. The gamma secretase inhibitor (JSMD194) can increase surface BCMA expression and decrease soluble BCMA.